2022
DOI: 10.1177/17456916211053319
|View full text |Cite
|
Sign up to set email alerts
|

The Cooperation Databank: Machine-Readable Science Accelerates Research Synthesis

Abstract: Publishing studies using standardized, machine-readable formats will enable machines to perform meta-analyses on demand. To build a semantically enhanced technology that embodies these functions, we developed the Cooperation Databank (CoDa)—a databank that contains 2,636 studies on human cooperation (1958–2017) conducted in 78 societies involving 356,283 participants. Experts annotated these studies along 312 variables, including the quantitative results (13,959 effects). We designed an ontology that defines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 67 publications
0
36
0
Order By: Relevance
“…Furthermore, the study samples were mostly college students, and college demographics have changed in the United States over the past several decades, to include more women and minorities (Anderson, 2003; Becker et al, 2010). That said, prior research has not found that cooperation varies by gender (Balliet et al, 2011; Spadaro, Jin, et al, 2022) or according to ethnicity in the United States (meta-analytic summary provided in the CoDa; Spadaro et al, in press). In addition, we found no significant difference in cooperation between student and nonstudent samples, and that the overall pattern of an increase of cooperation over time did not change when controlling for student sample (see the ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the study samples were mostly college students, and college demographics have changed in the United States over the past several decades, to include more women and minorities (Anderson, 2003; Becker et al, 2010). That said, prior research has not found that cooperation varies by gender (Balliet et al, 2011; Spadaro, Jin, et al, 2022) or according to ethnicity in the United States (meta-analytic summary provided in the CoDa; Spadaro et al, in press). In addition, we found no significant difference in cooperation between student and nonstudent samples, and that the overall pattern of an increase of cooperation over time did not change when controlling for student sample (see the ).…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation is that behavior and outcomes within experimental social dilemmas do not allow us to infer which psychological processes and motives (e.g., values, beliefs, and self-concept) are changing over time in American society to produce these changes in behavior. Importantly, cooperation in social dilemmas, including the studies reported in the CoDa (Spadaro et al, in press), can be used to test many other theories about cooperation and prosocial behavior that are not addressed in the present work, such as understanding prosocial personality (Thielmann et al, 2020), how institutional rules affect cooperation (Jin et al, 2021), how cooperation varies across regions, countries, and cultures around the world (Spadaro, Graf, et al, 2022). The annotation of these studies has been made open access for researchers to use to test hypotheses and answer research questions about cooperation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations